Analisis Faktor-faktor yang Memengaruhi Tingkat Kepatuhan Membayar Zakat: Studi Kasus Kabupaten Bogor - Ahmad Mukhlis; Irfan Syauqi Beik (AL-MUZARA'AH, 2013)
Poverty is one of major problems faced by Indonesia. The economic crisis occured within the country and around the world has lengthened the poverty disaster attacking Indonesia. To overcome these problems, zakat is likely to be an alternative solution that can be utilized by government. Zakat is a means legalized by Islam in capital formation. Capital formation is not solely based on utilization and development of natural resources, but also from obligatory contributions of the rich. Zakat is also playing significant role in improving the quality of human resources and the provision of facilities and infrastructure of production. The potential zakat of Indonesia exceeds Rp 217 trillion, but in reality the absorption of zakat funds reached Rp 1.5 trillion in 2010. The huge gap between the potential and the actual collection of zakat indicates that there are some Muslims who are less motivated to pay zakat. The purpose of this study is to identify factors that affect compliance level of paying zakat, and to identify the dominant factors, in order to more easily create optimal policy. Results from this study are expected to help increase acceptance of zakat, both at central and regional levels. Data is collected through a survey of 100 respondents in Bogor regency. The analytical method used is factor analysis. The program used to analyze the data is SPSS Statistics 17 for Windows. From these results, it is known that factors affecting willingness to pay the zakat are: religious factors, such as faith, religious understanding, and rewards; and other factors such as social awareness, self-satisfaction, and organizations. This also gives guidance that in order to increase zakat revenue, emphasis not only on religious aspect, but also on social, self-satisfaction, and organization aspects is very important. Among the variables that affect compliance level of paying zakat is the role of amil organization (OPZ). OPZ professionalism can strengthen regularity of zakat payer to pay zakat at OPZ. Improving the quality of OPZ in terms of transparency, socialization, and administration, will significantly affect the preferences of zakat payers to fufill their obligation at the amil institutions.